The usefulness of neutrophil to lymphocyte ratio in febrile seizure - A., Pooja; Aroor, Amitha Rao; Soans, Santosh T. (International Journal of Contemporary Pediatrics, 2020)
Background: Febrile seizure is an event in infancy or childhood, usually occurring between 3 months and 5 years of age associated with fever but without evidence of intracranial infection. The aim of the study was to estimate the usefulness of neutrophil-to-lymphocyte ratio (NLR) in patients with simple and complex febrile seizures. Methods: Retrospective case control study was done in a paediatric in patients admitted to tertiary care hospital. Study period was from January 2017 to December 2019. 200 children were analysed in the study. 100 out of 200 were under control group (febrile children without seizure). Remaining 100 were under case group (children with febrile seizure), 54 out of 100 children had complex febrile seizure, 46 out of 100 had simple febrile seizure. NLR ratio was done in all children. Results: Total 200 children were analysed in this study. High NLR ratio was noted among the cases (87 out of 100) compared to control (30 out of 100) p value = <0.001. Among the cases CFS had high NLR ratio compared to SFS, however p value was not significant (0.072). Conclusions: Children with febrile seizure had high NLR ratio compared to those without seizures. However no significant difference was noted between those with simple febrile seizure and complex febrile seizure However, larger trials are required to assess whether higher NLR can be taken as an independent risk factor for febrile seizure.